2019
DOI: 10.1111/acel.12969
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular adipose tissue‐derived stromal cells contribute to vascular remodeling during aging

Abstract: Aging is an independent risk factor for vascular diseases. Perivascular adipose tissue (PVAT), an active component of the vasculature, contributes to vascular dysfunction during aging. Identification of underlying cell types and their changes during aging may provide meaningful insights regarding the clinical relevance of aging‐related vascular diseases. Here, we take advantage of single‐cell RNA sequence to characterize the resident stromal cells in the PVAT (PVASCs) and identified different clusters between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 37 publications
(39 reference statements)
3
27
0
Order By: Relevance
“…Diagnostic performance of DeepFFR technique has been confirmed as previously described [10]. By learning corresponding invasive FFR values of coronary lesions from a large number of existing databases, this AI-based technology could generate neural network model by deep learning algorithm.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Diagnostic performance of DeepFFR technique has been confirmed as previously described [10]. By learning corresponding invasive FFR values of coronary lesions from a large number of existing databases, this AI-based technology could generate neural network model by deep learning algorithm.…”
Section: Discussionsupporting
confidence: 63%
“…When subjects are randomized to the CCTA/CT-FFR arm, on-site FFR based on the CCTA imaging (DeepFFR V1.0.0, Beijing CuraCloud Technology Co., Ltd., Beijing, China) will be measured. DeepFFR workstation is very dedicated software utilizing the original CCTA imaging to meter simulated FFR values in artificial intelligence (AI) model, which has been introduced in previous article [10]. The calculation process could be summarized as follows: the first step is to extract a 3D coronary artery model and generate coronary centerlines which are similar to the routine reconstruction of CCTA.…”
Section: Measurementmentioning
confidence: 99%
“…Nevertheless, it has since been discovered that PVAT regulates vascular tone, both through contractile and anticontractile regulation, vessel pathobiology in inflammation, angiogenesis, neointimal formation, and vascular fibrosis. 81 PVAT dysfunction is promoted by vascular injury, aging, obesity, and metabolic syndrome, and may impact adventitial remodeling during the early stages of vascular injury. 82 Communication between cells in the PVAT and cells residing in the other layers of the blood vessel wall occurs through the VV or through paracrine signaling.…”
Section: Cell and Ecm Changes In The Adventitia In Diseasementioning
confidence: 99%
“…The differentiation capacities of PVAT-derived stromal cells (PVASCs) are altered during aging. Also, the deletion of PGC-1α (proliferator-activated receptor-gamma and coactivator 1 alpha) in aged PVASCs exacerbates arterial remodeling and attenuates the browning of adipose tissue [82]. A recent study has revealed that the mineralocorticoid receptor (MR) is activated in the mitochondria of PVAT in obese mice, which causes premature-aging in adipose tissue and senescence, resulting in the loss of the anticontractile effects [83].…”
Section: Aging and Pvat Dysfunctionmentioning
confidence: 99%